(untitled) (Research, Society and Development, 2020)
The work aims to reflect and to describe the experience of the pediatric oncologist nurse in palliative care during home care assistance of mothers of children who have died of cancer at home. This is a descriptive study of the experience of nursing care at a federal public hospital, located in the city of Rio de Janeiro, during home care assistance of bereaved mothers of children with cancer in palliative care. A home nursing assistance script was prepared for the taken care of bereaved mothers, according to the phases of bereavement described by Bowlby. Eleven home nursing consultations were made to three mothers. Mothers had the opportunity to take care of their children in the last days of life. In the process of bereavement, the mothers went through the numbness or shock, the longing or search for the lost figure, the disorganization/dispersion and reorganization, often present themselves in the nursing consultations. The suffering of the mother requires the nurses to intervene in the process of mourning from a biopsychosocial and spiritual perspective. It is necessary that the nurses understand the situation of suffering, outlining strategies for caring for bereaved mothers. However, working with the grieving situation requires from the nurses´ empathy and bond of care to support the relatives at the moment of their losses, because they need to be welcomed, listened to, supported.